Suitable drying model for infrared drying of carrot - Togrul, Hasan (Elsevier Sci Ltd, 2006)
In this study, infrared drying characteristic of carrot was investigated in the temperature range of 50-80 degrees C. The strong influence of drying temperature on drying rate at early stage of drying was evident. Drying rate almost doubled when the drying temperature was increased from 50 to 80 degrees C. Five empirical drying models (Newton, modified Page, logarithmic, diffusion approach and Midilli model), given in literature for describing time dependence of the moisture ratio change were fitted to experimental data and model parameters in equations were determined by multiple regression analysis. By using of constant and coefficient determined in this study, the change of moisture ratio with time can be described by Midilli model in temperature range of 50-80 degrees C. The variation of model parameters with temperature described as exponential and power type. By using these verifications of parameters, thirty-eight drying models for describing combine effects of temperature and drying time was derived and the parameters of these models were also determined by multiple regression analysis. In case of the model include the combine effects of drying time and drying temperature, the model derived from Midili model give the best result. Effective diffusion coefficient in the temperature range 50-80 degrees C was determined as, 7.295 x 10(-11), 9.309 x 10(-11), 1.140 x 10(-10), 1.501 x 10(-10) m(2)/S, respectively. Activation energy was determined as 22.43 kJ/mol. (c) 2005 Elsevier Ltd. All rights reserved.
16th International Congress of Chemical and Process Engineering (CHISA) -- AUG 22-26, 2004 -- Prague, CZECH REPUBLIC
Keywords: carrot; infrared drying; mathematical model; statistical test